ChemInform Abstract: Zintl‐Phase Sr3LiAs2H: Crystal Structure and Chemical Bonding Analysis by the Electron Localizability Approach. Issue 51 (December 2015) - Feng, Xian‐Juan; Prots, Yurii; Bobnar, Matej; Schmidt, Marcus Peter; Schnelle, Walter; Zhao, Jing‐Tai; Grin, Yuri
Abstract: Sr3 LiAs2 H is prepared by melting and sintering of the elements and LiH in the molar ratio of Sr:LiH:Li:As = 3:1:1:2 (Ta crucible, 1.